2009
DOI: 10.3109/17482620903106645
|View full text |Cite
|
Sign up to set email alerts
|

The altered body after breast cancer surgery

Abstract: When a woman is ill with breast cancer and her body is under threat, she may feel as if she is losing her identity and life. The body has a central role in the female identity in Western societies. The aim of the study was to describe how Swedish women experience their altered bodies after breast cancer surgery. A refl ective lifeworld approach within the perspective of caring science was used. Ten women (aged 43-62 years) were interviewed and told their stories of the body retrospectively following breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 33 publications
0
33
0
1
Order By: Relevance
“…Besides increased bodily awareness, the women's lack of knowledge and understanding of their altered bodies was associated with a personal feeling of loss of control (Olesen et al., ), and a need for information and supervision from an early stage (Lindgren et al., ; Sekse et al., ). In the case of breast cancer, several studies (Arman & Rehnsfeldt, ; Lindwall & Bergbom, ; Thomas‐MacLean, ) have shown that knowledge and understanding are fundamental in the process of becoming confident and familiar with the altered body. Lindwall and Bergbom () found that women regarded their body as “a stranger” and that they had to process and regain familiarity with their altered bodies after breast cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Besides increased bodily awareness, the women's lack of knowledge and understanding of their altered bodies was associated with a personal feeling of loss of control (Olesen et al., ), and a need for information and supervision from an early stage (Lindgren et al., ; Sekse et al., ). In the case of breast cancer, several studies (Arman & Rehnsfeldt, ; Lindwall & Bergbom, ; Thomas‐MacLean, ) have shown that knowledge and understanding are fundamental in the process of becoming confident and familiar with the altered body. Lindwall and Bergbom () found that women regarded their body as “a stranger” and that they had to process and regain familiarity with their altered bodies after breast cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Lindwall and Bergbom (2009) have indicated that this kind of treatment might cause a woman to objectify her own body and to experience it as a "stranger." Although we agree with the observation that breast surgery might result in objectifying one's own body, we think that it cannot be claimed a priori that body objectification is undesirable.…”
Section: Phenomenology Of the Bodymentioning
confidence: 97%
“…According to Aristotle (2009), man should not focus on what is the right or wrong actions, but on which good act she, as a virtuous person, will perform. Dignified care does not merely entail medical treatment, but also shaping of an encounter and a conversation with the patient (Lindwall and Bergbom 2009). An ethical act means doing good, according to Aristotle (2009).…”
Section: Introductionmentioning
confidence: 99%